(untitled) (Journal of Hama University, 2024)
Abstract: The need for quick knowledge of the working behavior of concrete structures while they are exposed to various loads has become extremely important. Computer modeling programs that rely on the finite element method allow for computer representation of the behavior of concrete structures and thus quick knowledge of their behavior during work, which allows choosing the optimal design parameters before construction and knowing the facility’s need For maintenance after a period of use by analyzing the various reinforcement options and their impact on performance. This article presents the advantages of using the finite element program ANSYS to study the behavior of concrete structures, by modeling the behavior of a reinforced concrete beam, subjected to several types of load. To ensure the Validity of the computer model for the beam, the results taken from the previous modeling will be compared with the results of the analytical calculation, by solving the known traditional structural equations, as well as by comparison with the results taken from the calculations on the computational cloud uploaded on the website Clearcalcs.com, which specializes in construction calculations. In the end, the conclusion was reached that modeling of concrete structures using the ANSYS finite element program can be adopted as an effective method for studying the behavior of these structures, whether in the design stages or in the maintenance stage, and through it we will obtain results that are close to the experimental results.